Efficacy and Safety of Remdesivir in COVID-19 Positive Dialysis Patients - Batool Butt; Tajamul Hussain; Mu'taman Jarrar; Kashaf Khalid; Waleed Albaker; Asma Ambreen; Yasir Waheed (MDPI AG, 2022)
(1) Background: Immune compromised hemodialysis patients are more likely to develop COVID-19 infections, which increase the risk of mortality. The benefits of Remdesivir, despite less literature support on its effectiveness in dialysis patients due to renal toxicity, can outweigh the risks if prescribed early. The aim of this study was to evaluate the efficacy of Remdesivir on the 30-day in-hospital clinical outcome of hemodialysis population with COVID-19 infection and safety endpoints of adverse events. (2) Study design: A prospective quasi-experimental study design was used in the study. (3) Methods: The sample population consisted of 83 dialysis patients with COVID-19 who were administered Remdesivir at a dose of 100 mg before hemodialysis, as per hospital protocol. After the treatment with Remdesivir, we assessed the outcomes across two endpoints, namely primary (surviving vs. dying) as well as clinical and biochemical changes (ferritin, liver function test, C-reactive protein, oxygen requirements, and lactate dehydrogenase levels) and secondary (adverse effects, such as diarrhea, rise in ALT). In Kaplan-Meier analysis, the survival probabilities were compared between patients who received Remdesivir within 48 h of diagnosis and those who received it after 48 h. Cox regression analysis was employed to determine the predictors of outcome. (4) Results: Of the 83 patients, 91.5% survived and 8.4% died. Remdesivir administration did not reduce the death rate overall. Hospital stays were shorter (p = 0.03) and a nasopharyngeal swab for COVID-19 was negative earlier (p = 0.001) in survivors who had received Remdesivir within 48 h of diagnosis compared to those who had received Remdesivir after 48 h. The only variables linked to the 30-day mortality were serum CRP (p = 0.028) and TLC (p = 0.013). No major adverse consequences were observed with Remdesivir. (5) Conclusions: Remdesivir has the potential to shorten the recovery time for dialysis patients if taken within 48 h of onset of symptoms, without any adverse effects.